Passing Values, Building Identity: An Intergenerational Value Transmission and Shared Identity in East Nusa Tenggara Christian Families - Chatarin Angelina Balle; Nuke Martiarini (Psikostudia : Jurnal Psikologi, 2026)
Christian families in East Nusa Tenggara are known for their strong family values. However, the effectiveness of value transmission within the family faces challenges due to changing times and shifts in domestic relationship dynamics. This study aims to empirically analyze the influence of family values transmission on shared family identity among Christian families in East Nusa Tenggara. Utilizing a quantitative approach with a cross-sectional survey design, this study involved 197 mothers selected through purposive sampling. Data were collected using the Transmission of Values Scale (21 items) and the Shared Family Identification Scale (5 items), and subsequently analyzed using simple and multiple linear regression tests. The results indicate that family values transmission has a positive and significant effect on shared family identity (B=0.194; p<0.001), contributing 33.3% to the variance. Additionally, the demographic variable of marriage duration was also found to have a positive and significant effect on shared family identity (B=0.378; p<0.001). These findings underscore that the effectiveness of value transmission within the household plays a crucial role in strengthening a collective family identity among Christian families. This study highlights the urgency of strengthening the family's role, particularly that of the mother, in transmitting core values as an effort to reinforce family identity amidst ongoing social changes.Keluarga Kristen di Nusa Tenggara Timur dikenal memiliki nilai kekeluargaan yang kuat, namun efektivitas pewarisan nilai dalam keluarga menghadapi tantangan akibat perubahan zaman dan dinamika relasi keluarga. Penelitian ini bertujuan menganalisis pengaruh family values transmission terhadap shared family identity pada keluarga Kristen di Nusa Tenggara Timur. Dengan menggunakan pendekatan kuantitatif dengan desain survei cross-sectional, studi ini melibatkan 197 ibu sebagai partisipan yang dipilih menggunakan teknik purposive sampling. Pengumpulan data menggunakan Transmission of Values Scale (21 item) dan Shared Family Identification Scale (5 item), yang kemudian dianalisis melalui uji regresi linier sederhana dan berganda. Hasil penelitian menunjukkan bahwa family values transmission berpengaruh positif dan signifikan terhadap shared family identity (B = 0.194; p < 0.001) dengan kontribusi sebesar 33.3%. Di samping itu, variabel demografis usia pernikahan juga ditemukan berpengaruh terhadap shared family identity (B = 0.378; p < 0.001). Rangkaian temuan ini menegaskan bahwa efektivitas transmisi nilai dalam keluarga berperan penting dalam memperkuat identitas keluarga bersama pada keluarga Kristen. Hasil penelitian ini mengindikasikan pentingnya penguatan peran keluarga, khususnya ibu, dalam mentransmisikan nilai-nilai keluarga sebagai upaya memperkuat identitas keluarga di tengah perubahan sosial yang terus berkembang.